Hot-hole-induced dielectric breakdown in LDMOS transistors. - Labate, L.
A novel failure mechanism in an n-channel lateral double-diffused metal-oxide-semiconductor (LDMOS) transistor biased in the saturation mode is investigated. A correlation between time-to-breakdown and hot hole gate current is established and the static safe operating area (SOA), limited by hot-hole-induced dielectric breakdown, is defined. A method based on the evaluation of the time integral of an "effective" hot-hole gate current is proposed which allows us to estimate the time-to-fail of the device operating in any dynamic (periodic) mode, beyond its static SOA. The prebreakdown degradation of some electrical parameters, attributed to hot hole injection into the gate oxide, is also discussed.
Keywords: HV devices; Dynamic mode; Electrical parameters; Failure mechanism; Gate oxide; High-voltage devices; Hot hole gate current; Hot hole injection; Hot-hole-induced dielectric breakdown; Lateral double-diffused MOS transistor; N-channel LDMOS transistor; Periodic mode; Prebreakdown degradation; Saturation mode; Static SOA; Static safe operating area; Time-to-breakdown.